CIVIL AND ECONOMIC PROCEDURAL LAW IS A SOLID FOUNDATION FOR FAIR TRIAL AND LEGAL PROTECTION. (International journal of artificial intelligence, 2025)
This article discusses the content and essence of civil and economic procedural law, the principles of fair trial, the improvement of legal protection mechanisms and their compliance with international standards in our national legislation. The article is devoted to the urgency of forming a fair judicial system within the framework of the judicial and legal reforms underway in the Republic of Uzbekistan.